Hot deformation and acicular ferrite microstructure in c-mn steel containing Ti2O3 inclusions - Shim, JH; Byun, JS; Cho, YW; Oh, YJ; Shim, JD; Lee, DN (IRON STEEL INST JAPAN KEIDANREN KAIKAN, 2000)
The influence of hot deformation on the formation of acicular ferrite in C-Mn wrought steels containing Ti2O3 inclusions has been investigated, A significant amount of acicular ferrite is formed even after hot deformation. From this, it seems that the ability of Ti2O3 inclusions to induce the nucleation of intragranular fer rite remains valid within recrystallized austenite grains after deformation. However, the fractions of acicular ferrite are lower than those in the steels without hot deformation. A high fraction of acicular ferrite is obtained after hot deformation when Mn level is high, the formation of intergranular ferrite such as allotriomorphic ferrite and upper bainite being pronouncedly suppressed. Deformation at relatively low temperatures discourages the formation of acicular ferrite while encouraging intergranular ferrite by reducing prior austenite grain size and consequently by increasing the area of the austenite grain boundaries.